Communication interference in sympatrically occurring moth species - Juárez, María Laura (2016)
In moth species, females emit a species‐specific sex pheromone that is perceived over long distance by conspecific males. The species‐specificity in the chemical communication channel is achieved by a combination of unique components in specific ratios and sometimes also by interspecific behavioural antagonists to deter sympatrically occurring heterospecific males. In this study, we determined possible antagonistic effects in Helicoverpa gelotopoeon Dyar (Lepidoptera: Noctuidae) males to the major sex pheromone component of sympatrically occurring heliothine moths, Z11‐16:Ald, as well as to the sex pheromone of the sympatrically occurring Heliothis virescens (Fabricius) (Lepidoptera: Noctuidae) (Z11‐16:Ald and Z9‐14:Ald). We also explored whether other co‐occurring species are attracted to these pheromone blends. Our field experiments showed that the addition of Z11‐16:Ald alone or in combination with Z9‐14:Ald inhibited trap catches of H. gelotopoeon males and that this inhibition depended on the concentration of these compounds. In addition, other moth species were attracted to the blends. Together, our results confirm the antagonistic effect of heterospecific sex pheromone compounds of H. virescens to H. gelotopoeon.